O jornalismo local e a reportagem multimodal como ferramentas de educação midiática: um estudo de caso da Agência Mural - Rosendo, Ana Júlia Storti (Universidade Federal de São Carlos, 2025)
With the rise and popularization of social networks, different parts of the globe are increasingly connected through technology, enabling the accelerated dissemination of information to anyone and everyone, an activity that was previously the domain of journalists, professionals committed to fact-checking before reporting them. With the absence of this commitment to information, there is a growing circulation of misinformation, or fake news, especially in Brazilian municipalities where there is no official media outlet, that is, in the so-called news deserts. Therefore, this work seeks to understand the importance of media literacy in combating this social problem, mainly through local journalism and multimodal reporting, which reach a larger number of readers. To achieve these objectives, the methodology involves a case study of the special report "Sem Notícias" (Without News), produced by Agência Mural, on news deserts and the impacts of misinformation on people's lives, and interviews with a journalist responsible for the news. The study observes that new journalistic textual architectures are important for information to reach a wider audience, and that classroom activities can be considered potential media literacy initiatives, helping to combat misinformation.
Local journalism and multimodal reporting as media literacy tools: a case study of Agência Mural
Keywords: jornalismo local; Deserto de notícias; Multimodalidade; Educação midiática; Local journalism; News desert; Multimodality; Media literacy; LINGUISTICA, LETRAS E ARTES; 4. Educação de Qualidade; 12. Consumo e Produção Responsáveis; 16. Paz, Justiça e Instituições Eficazes; 17. Parcerias e Meios de Implementação; 18. Igualdade Étnico-Racial para o Desenvolvimento Sustentável